Unpacking Sino-Central Asian engagement along the New Silk Road: a case study of Kazakhstan. Issue 2 (3rd July 2018) - Bitabarova, Assel G.
ABSTRACT: Background . Although China's Belt and Road Initiative (BRI) has received increasing attention at the global level, there is, however, little information about how and with what implications it is being enacted on the ground. This is partly because existing scholarship has primarily focused on Chinese interests and motives behind the grand proposal, while perspectives of other countries participating in the BRI remain understudied.Purpose . The study seeks to bridge this gap by contextualizing the land-based component of the BRI, Silk Road Economic Belt (SREB), in Central Asia. Its purpose is two-fold: (1) to discuss how Beijing perceives the role of Central Asia in general and Kazakhstan in particular in advancing its New Silk Road proposal; (2) to explore how the SREB is being implemented and perceived in Kazakhstan, where it was first announced in September 2013. In particular, it offers a detailed account of how Kazakhstan is trying to integrate its infrastructure development program " Nurly Zhol" for 2015-2019 into the SREB, which is missing from the current scholarly literature.Main Argument . The paper argues that, notwithstanding power asymmetries, the BRI participant/recipient countries do have the agency to develop their own agenda and relevant policies for interactions with Beijing.Conclusion . The case study analysis suggests that there is little evidence that China unilaterally imposes its agenda upon Kazakhstan. Moreover, a shared understanding between the two states about the complementarity of mutual interests provides a solid foundation for overall Kazakh-Chinese cooperation. Yet, the strengthening of relations between the two neighbors, especially in the economic domain, has not led to an improvement of Kazakh popular perceptions of China, whose image is further worsened by the ongoing securitization of ethnic minorities in Xinjiang, including Kazakhs.